Exploring the Teaching Skills and Needs of Studio Piano Teachers with Mature Aged Students in Halifax, Nova Scotia - McMillan, Jan (Malaysian Journal of Music, 2016)
Connecting piano teachers who work in isolated situations with recent research and training is difficult, especially when accreditation, registration with professional bodies, training or ongoing professional development is not mandatory. In previous Australian and international studies, many piano teachers have reported that they do not feel comfortable teaching adults who have reported difficulty finding suitable teachers. Historically, piano performance qualifications have excluded pedagogical training particularly for adults. Current trends defer pedagogical studies to the postgraduate level whilst piano teachers have requested it at earlier stages of their training. To solve these issues within the piano teaching industry, this study set out to examine the teaching skills and needs of both piano teachers and their adult students in Halifax, Nova Scotia, Canada. Qualitative data was collected using face-to-face meetings, email, questionnaires, student journals, teacher reflections, videos and skype interviews. The study produced a set of guidelines for teaching adults that addressed the research criteria. Existing teaching skills emerged in five subthemes: Performance Related Skills, Personal Skills, Teaching Approaches, Student Learning Styles, and Teaching Strategies. The teacher’s needs included andragogic training at earlier levels of study, guidelines for adult students, business practices, expanded professional development opportunities and a repertoire for adult students. Students confirmed the need for flexibility, understanding teachers, less performance and technical skills, facilitative or dictatorial roles relating to skill levels, practice schedules and demonstration of repertoire and practice skills. The study concluded that inclusion of andragogic studies better prepares teachers for increasing numbers of adult learners.